Syukur Sebagai Fondasi Nilai-Nilai Pendidikan Islam: Studi Al-Qur'an Surat Al-Fatihah, Surat Luqman Ayat 12, dan Surat Ibrahim Ayat 7 - Andryan Fitryansyah Muhammad (Al-Fath, 2023)
The teachings and instructions of the Qur'an relate to various concepts that are really needed by humans in navigating their lives in this world and in the hereafter. Gratitude is considered one of the foundations of Islamic education. Islamic education aims to instill values ​​such as faith, worship and morals in individuals to become better humans. The type of research that the author uses in this research is literature study. In life, no matter how small something we receive we should be grateful. Unfortunately, not everyone is able to direct the thoughts in their minds to always be grateful for what we get every day. Al-Qur'an There are many benefits from being grateful and there are also many bad things if we are not grateful. The Qur'an also explains that gratitude is a result and goal of the creation of the universe and also the most important result of the creation of living creatures is gratitude to Allah SWT.